Prenatal diagnosis, management and challenges of fetal defects: an epidemiological survey in a low-income Country - Ndiaye, Mame Diarra; Cisse, Lissoune; Traore, Mamadou; Ndour, Daouda; Faye, Pape Moctar; Mbaye, Maguette; Leye, Mouhamed; Chami, Helene; Gueye, Mamour (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The objective of this study was to describe the epidemiology and outcomes of fetal anomalies and malformations in a low-income country. Methods: This was a descriptive, retrospective, cross-sectional study conducted over 18 months in various hospitals in Senegal. All fetuses diagnosed with a structural or functional fetal anomaly were included. Cases presenting with intrauterine fetal death (IUFD) were excluded, due to lack of ultrasound diagnosis. Data were collected via a database using Filemaker® software and analyzed using Statistical Package for Social Sciences version 20.0 (SPSS). Qualitative variables were described by proportions, while quantitative variables were expressed using their dispersion parameters. Results: A total of 155 cases of fetal pathologies were recorded. The anomalies primarily affected the central nervous system (20.6%), the urinary system (51%), the musculoskeletal system (11.6%), the abdomen and digestive tract (11.3%), and the heart (11%). Among the fetuses, 57 (36.8%) had in utero complications, with 13 cases of intrauterine fetal death (8.8%). Invasive diagnostic procedures were performed on 15 patients (9.7%), and antenatal treatment was administered to 10 patients (6.5%). The mean gestational age at delivery was 35.6 weeks. Caesarean delivery was predominant (76.3%). Postnatal care was medical for 43 patients, surgical for 26, and palliative for 22. Neonatal mortality was 51.4%. Among this neonatal death, 30% of cases linked to the lack of postnatal care. Conclusions: The prevalence of fetal malformations remains stable and similar across countries. The organization of prenatal diagnosis and specialized care must be a priority.